Sistem Pakar IQ dalam Pengelompokan Anak Reterdasi Mental dengan Algoritma K-Means - Novi Rahayu (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
Reterdated mental children are children who have an intellectual level below the average. mentally retarded children are children who have intellectual deficiencies or limitations, are below the normal average, so have difficulties in academic, communication, and social tasks, and require special education services. Expert system is one part of artificial intelligence which has recently experienced very rapid development. This study aims to help the Dharma Wanita Extraordinary School to place students and students into a class with groups that are equally backward by applying the K-Means algorithm. The design of this expert system uses Data Flow Diagrams (DFD) and the programming language used to build expert systems in this study is Visual Basic. The results of the expert system built in this study help in diagnosing the level of mental reterdation based on the symptoms given by the user and the level of mental reterdation based on possible values ​​using the K-Means algorithm calculation. Keywords:Expert System, Mental Retarded Children, K-Means Algorithm.